Krise und Krisenerfahrung: Unternehmensstrategien und Arbeitsverhältnisse in der deutschen Werftindustrie 1976 bis 1990; Crisis and Crisis Experience: Corporate Strategies and Employment Changes in the German Shipbuilding Industry 1976 to 1990 - Katharina Bohte; Harald Wixforth (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte (VSWG), 2025)
– This article examines the interrelation between corporate strategies, employment changes and workers' experiences in the German shipbuilding industry in the light of economic crisis. From the middle of the 1970s onwards, due to global economic crisis and global competition this originally large-scale industry evolved into a medium-sized high-technology sector. Against this backdrop, the study reveals different management strategies of shipyards in the northwest of Germany and how these implicated employment structures and working conditions. Based on oral history interviews with shop floor workers and engineers in the construction offices, individuals' narrations show diverse experiences of work degradation and subjective implications on different workers' roles, positions and realities.
Keywords: N34; 330; shipbuilding industry; shipyard crisis; corporate strategies; employment structures; working conditions; workers' experiences